Case Study 1 - Bangalore, India : Participatory Approaches in Budgeting and Public Expenditure Management - World Bank (Washington, DC, 2012)
Inspired by a private sector practice of conducting client satisfaction surveys, a small group of people in Bangalore2, concerned about the city' deteriorating standards of public services3, initiated an exercise in 1993 to collect feedback from users. User perceptions on the quality, efficiency, and adequacy of the various services were aggregated to create a 'report card' that rated the performance of all major service providers in the city. The findings presented a quantitative measure of satisfaction and perceived levels of corruption, which, following coverage in the media, not only mobilized citizen and government support for reform, but also prompted the rated agencies themselves to respond positively to civic calls for improvement in services. This exercise was repeated in 1999, and has been replicated in at least five other Indian cities, as well as the State of Karnataka in the interim. By systematically gathering and disseminating public feedback, report cards may serve as a "surrogate for competition" for monopolies - usually government owned - that lack the incentive to be as responsive as the private enterprises to their client's needs. They are a useful medium through which citizens can credibly and collectively 'signal' to agencies about their performance and pressure for change.